2021
DOI: 10.3390/polym13142315
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced and Nanofiber-Nucleated Crystallization of Novel Aliphatic–Aromatic Copolyesters Delineated for In Situ Generation of Biodegradable Nanocomposites

Abstract: The shear-induced and cellulose-nanofiber nucleated crystallization of two novel aliphatic–aromatic copolyesters is outlined due to its significance for the in situ generation of biodegradable nanocomposites, which require the crystallization of nanofibrous sheared inclusions at higher temperatures. The shear-induced non-isothermal crystallization of two copolyesters, namely, poly(butylene adipate-co-succinate-co-glutarate-co-terephthalate) (PBASGT) and poly(butylene adipate-co-terephthalate) (PBAT), was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The shear-induced and cellulose-nanofiber nucleated crystallisation were investigated. The author reported that the addition of CNFs did not influence the PBAT crystallinity degree but contributed to the strong increase in the crystallisation temperature [19]. Active packaging films based on nanocomposites of PBAT and cellulose nanofibers (CNS, 5 wt.%) encapsulated with eugenol and linalool were studied.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The shear-induced and cellulose-nanofiber nucleated crystallisation were investigated. The author reported that the addition of CNFs did not influence the PBAT crystallinity degree but contributed to the strong increase in the crystallisation temperature [19]. Active packaging films based on nanocomposites of PBAT and cellulose nanofibers (CNS, 5 wt.%) encapsulated with eugenol and linalool were studied.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…An increase in storage modulus, dynamic viscosity and crystallinity was achieved [18]. Hosseinnezhad studied the action of different shear rates on the crystallisation of biodegradable nanocomposites of poly(butylene adipate-co-succinate-co-glutarate-co-terephthalate) poly(butylene adipate-co-terephthalate) (PBAT) filled with cellulose nanofiber [19]. The authors reported induced nucleation upon shearing coexisting with quicker crystallisation, higher density nucleation sites, and thinner lamella stacks.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The presence of nanoparticles in the polymer matrix not only influences the crystallization behavior, but also modulates the polymer response to the applied shear, especially when the nucleating nanoparticles are incorporated into the polymer matrix. 8,9 The carbon nanoparticles, including carbon black, carbon fiber, graphite, and carbon nanotube (CNT), in addition to controlling the crystallization behavior, impart electrical conductivity to the polymer. [10][11][12] In this case, shearing affects the electrical conductivity in addition to crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al 12 have reported several microorganisms and their respective enzymes which could degrade aliphatic, aromatic, as well as aliphatic‐aromatic co‐polyesters like poly(butylene succinate) (PBS), poly(butylene succinate)‐co‐(butylene adipate) (PBSA), poly(ε‐caprolactone) (PCL), poly(ethylene succinate) (PES), poly(L‐lactic acid) (PLA), poly(3‐hydroxybutyrate) (PHB) and poly(3‐hydoxybutyrate‐co‐3‐hydroxyvalterate) (PHB/PHBV), poly(ethylene terephthalate) (PET), poly(butylene terephthalate) (PBT), poly(butylene adipate‐co‐terephthalate (PBAT), poly(butylene succinate‐co‐terephthalate) (PBST), and poly(butylene succinate/terephthalate/isophthalate)‐co‐(lactate) (PBSTIL). To obtain biodegradable polymers with good mechanical properties, several aliphatic‐aromatic copolyesters such as PBAT have been prepared, analyzed and tested 13–17 …”
Section: Introductionmentioning
confidence: 99%
“…To obtain biodegradable polymers with good mechanical properties, several aliphatic-aromatic copolyesters such as PBAT have been prepared, analyzed and tested. [13][14][15][16][17] The research, preparation and evaluation of organicinorganic hybrid composites is valuable, since it can promote modifications in the original polymeric matrices, such as adding antimicrobial activity, changing thermal degradation temperature and dimensional stability, optical and water vapor barrier properties, wettability, physical and chemical resistance, and do not promote microplastic formation, when they are disposal in the proper place. The appropriate selection of composite elements, as well as their proportions and the obtaining method must be carried out for these changes to configure desired improvements.…”
mentioning
confidence: 99%